(untitled) (Huellas, 2025)
This research investigates the ways of living of the middle classes in peripheral areas of the Mendoza Metropolitan Area at the beginning of the 21st century, with the aim of contributing to the understanding of the reproduction of urban inequalities. Socio-spatial segregation and daily mobility are considered structuring phenomena of inequalities and are, therefore, key axes for observing ways of living. The methodology focused on conducting interviews with residents in selected areas. In conclusion, it is noted that middle classes adapt to the prevailing mercantilist dynamics and, although they manage to meet their material needs, they face contradictions, discontent, and dissatisfaction that restrict their full appropriation of space. These tensions can be the starting point for questioning current urban development in the search for more equitable and participatory alternatives.